A model coupling the effects of soil moisture and potential evaporation on the tree transpiration of a semi‐arid larch plantation. Issue 1 (19th August 2016) - Li, Zhenhua; Yu, Pengtao; Wang, Yanhui; Webb, Ashley A.; He, Cong; Wang, Yanbing; Yang, Lili
Abstract: Quantifying the tree transpiration (T) response to the coupling effects of changing soil moisture and weather conditions provides insights into water use by forests, especially in dryland regions. This study was conducted in a semi‐arid pure larch ( Larix principis‐rupprechtii ) plantation in northwest China. The sap flow density of trees, weather conditions in open field, and soil moisture of main root zone (0–60 cm) were measured synchronously and continuously throughout a growing season in 2010. The response of daily T to the relative extractable soil water (REW) and potential evapotranspiration (PET) was analyzed. The T varied in the range of 0.08–2.18 mm/day during the study period. With increasing REW, it initially rose quickly and almost linearly; but after the REW reached a threshold, it leveled off and gradually approached its maximum (Tmax ). However, Tmax positively related with PET. Based on the T‐REW and Tmax ‐PET relationships, an integrated model (T = (−0.05PET 2  + 0.65PET) × (1 −  exp (−5.39REW))) was developed to describe the complex T‐REW‐PET relationship and it fit the measured data well. For the whole study period, due to the limit of PET and REW, the actual T was reduced by 32% (88.6 mm) and 16% (45.0 mm) respectively, compared with potential T. Although this model cannot be widely applied until it is validated with measured data from more sites, it does provide a way to accurately estimate the daily T using REW and PET data and to quantify the coupling effects of changing REW and PET on the T.